Vision and Visual History in Elite/Near-Elite-Level Cricketers and Rugby-League Players - Brendan T. Barrett; Jonathan C. Flavell; Simon J. Bennett; Alice G. Cruickshank; Alex Mankowska; Julie M. Harris; John G. Buckley (Sports Medicine - Open, 2017)
Abstract Background The importance of optimal and/or superior vision for participation in high-level sports remains the subject of considerable clinical research interest. Here, we examine the vision and visual history of elite/near-elite cricketers and rugby-league players. Methods Stereoacuity (TNO), colour vision, and distance (with/without pinhole) and near visual acuity (VA) were measured in two cricket squads (elite/international-level, female, n = 16; near-elite, male, n = 23) and one professional rugby-league squad (male, n = 20). Refractive error was determined, and details of any correction worn and visual history were recorded. Results Overall, 63% had their last eye examination within 2 years. However, some had not had an eye examination for 5 years or had never had one (near-elite cricketers 30%; rugby-league players 15%; elite cricketers 6%). Comparing our results for all participants to published data for young, optimally corrected, non-sporting adults, distance VA was ~ 1 line of letters worse than expected. Adopting α = 0.01, the deficit in distance VA was significant, but only for elite cricketers (p < 0.001) (near-elite cricketers, p = 0.02; rugby-league players, p = 0.03). Near VA did not differ between subgroups or relative to published norms for young adults (p > 0.02 for all comparisons). On average, near stereoacuity was better than in young adults, but only in elite cricketers (p < 0.001; p = 0.03, near-elite cricketers; p = 0.47, rugby-league players). On-field visual issues were present in 27% of participants and mostly (in 75% of cases) comprised uncorrected ametropia. Some cricketers (near-elite 17.4%; elite 38%) wore refractive correction during play, but no rugby-league player did. Some individuals with prescribed correction choose not to wear it when playing. Conclusions Aside from near stereoacuity in elite cricketers, the basic visual abilities we measured were not better than equivalent, published data for optimally corrected adults; 20–25% exhibited sub-optimal vision, suggesting that the clearest possible vision might not be critical for participation at the highest levels in the sports of cricket or rugby league. Although vision could be improved in a sizeable proportion of our sample, the impact of correcting these, mostly subtle, refractive anomalies on playing performance is unknown.